Psychotropic stewardship: Advancing patient care - Haight Robert J. PharmD, BCPP; Di Polito Chelsea N. PharmD, BCPP; Payne Gregory H. MBA, CAE; Bostwick Jolene R. PharmD, BCPP, BCPS; Fulbright April PharmD, BCPP; Lister Jonathan F. PharmD, BCPP; Williams Andrew M. PharmD, BCPP (American Association of Psychiatric Pharmacists, 2023)
Board Certified Psychiatric Pharmacists (BCPPs) practice in a variety of inpatient and outpatient health care settings as part of collaborative, multidisciplinary teams. The American Association of Psychiatric Pharmacists (AAPP) has promoted the expansion of psychiatric pharmacy through the development of psychotropic stewardship programs (PSPs). Based on the standards developed during the creation and expansion of antimicrobial stewardship programs, psychotropic stewardship promotes the safe and appropriate use of psychotropic medications. AAPP envisions every patient with a psychiatric diagnosis will have their medication treatment plan reviewed, optimized, and managed by a psychotropic stewardship team with a psychiatric pharmacist as a co-leader. Because of variations in practice site resources, patient populations, and provider collaboration, the creation and implementation of PSPs should be based on site-specific needs and opportunities. Initial patient identification could prioritize those prescribed multiple medications, high-risk psychotropics, or comorbid medical diagnoses. However, every patient prescribed a psychotropic medication should have the opportunity to work with a PSP. Incremental implementation may be required during the planning stages of stewardship teams. Use of clinical practice-related core outcomes will allow for the optimization of program resources, increased recognition, and improved patient outcomes. PSPs should be patient-focused and integrate patients' preferences and access to recommended treatment options. The eventual goal of PSP implementation is official recognition by key regulatory agencies as a standard of care for patients who receive a diagnosis of a psychiatric or substance use disorder.